Talent identification and promotion programmes of Olympic athletes - Vaeyens, R.; Güllich, A.; Warr, C. R.; Philippaerts, R. (Journal of Sports Sciences, 2009)
The start of a new Olympic cycle offers a fresh chance for individuals and nations to excel at the highest level in sport. Most countries attempt to develop systematic structures to identify gifted athletes and to promote their development in a certain sport. However, forecasting years in advance the next generation of sporting experts and stimulating their development remains problematic. In this article, we discuss issues related to the identification and preparation of Olympic athletes. We provide field-based data suggesting that an earlier onset and a higher volume of discipline-specific training and competition, and an extended involvement in institutional talent promotion programmes, during adolescence need not necessarily be associated with greater success in senior international elite sport. Next, we consider some of the promising methods that have been (recently) presented in the literature and applied in the field. Finally, implications for talent identification and promotion and directions for future research are highlighted.